Technology-based empowerment and disaster resilience strengthening for coffee farmer groups in Donorejo Village, Purworejo - Adi Sucipto; Hesti Respatiningsih; Rusmiyatun Rusmiyatun; Suyitno Suyitno; Murry Harmawan Saputra; Jeki Mediantari Wahyu Wibawanti; Yoga Wicaksana; Singgih Maulana Wira Adi Saputra; Satrio Budi Aji; Aprilia Dewi Nurkhasanah; Talita Erina Tri Widyastuti (Community Empowerment, 2026)
Coffee farming is a major source of livelihood for rural communities, but its sustainability is threatened by weak managerial capacity, low technology adoption, and landslide risks. This community service activity aims to strengthen the economic independence of the “Bangun Semi” Coffee Farmer Group in Donorejo Village, Purworejo. The program was implemented using a Participatory Action Research (PAR) approach through the stages of socialization, training, technology application, mentoring, and evaluation. Interventions included digital bookkeeping training, strengthening the branding and digital marketing of Kopi Semi, installing a solar-powered coffee roasting machine, utilizing coffee husk waste into fermented animal feed, and implementing a Landslide Early Warning System (LEWS). The results showed an increase in business capacity and partner resilience. The selling price of coffee increased by more than 120%, roasting productivity rose from 2 kg/day to 12 kg/day, and energy costs decreased by up to 88%. In addition, the utilization of coffee husk waste reduced feed costs by up to 20%, while LEWS strengthened early warning and community preparedness. This integrated model is effective in strengthening a resilient local economic independence and has the potential to be replicated in other disaster-prone areas.